Social status qualifiers: dimensions and determinants of factors shaping social status for women and men in Sweden - Ulfsdotter Eriksson, Ylva; Larsson, Bengt (Frontiers in Sociology, 2024)
This study contributes to our understanding of what lifestyle factors affect the social status of women and men in contemporary postmaterialist societies. We examine the dimensions and determinants of social status qualifiers among Swedish people using a survey of 1,653 Swedish respondents who ranked the importance of 14 qualifiers for the social status of a woman and a man. The analysis showed surprisingly strong similarities in what factors affect the social status of women and menboth in the importance of individual status qualifiers and in the three underlying status dimensions: The highestranked dimension included status qualifiers related to external material resources and properties. The second most important dimension comprised interactional resources such as manners, looks, being married and having children. The third dimension concerned the importance of interest and engagement in politics, the environment, and fine art, which were of the least importance for social status. The few significant differences in ascriptions of status for a woman or a man were rather gender stereotypical.In addition, the analysis revealed some significant differences in status perceptions among the respondents: Gender, class, educational background, and country of birth were among the main determinants of such differences.